Meningkatkan Keterampilan Menulis dengan Media Buku Begaris Tiga pada Anak Berkesulitan Belajar Menulis - Paisal, Erix Al; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2021)
This study aims to prove whether children's skills in writing simple sentences increase after being given a three-line book media intervention to children with learning difficulties in class III at SDN 07 Binuang Kampung Dalam Padang. The type of research in this research is experimental research in the form of Single Subject Research (SSR) with an A-B-A design. In this study, the subject of the study was one child with learning difficulties in class III at SDN 07 Binuang Kampung Dalam Padang. In this study, the data collection techniques used were in the form of tests and documentation studies. The data analysis technique used is visual analysis of the graph. The results of data analysis from 16 meetings in 3 conditions, namely at baseline (A1) with data results of 0%, 0%, 0%, and 0%. In the intervention (B) with the results of the data 20%, 30%, 40%, 50%, 60%, 70%, 70%, and 70%. At baseline (A2) with 60%, 70%, 70%, and 70% data results. The results showed that simple sentence writing skills improved after being given the intervention of three-lined book media for children with learning difficulties in class III at SDN 07 Binuang Kampung Dalam Padang.